Cavarero’s Muse: The Troubling Power of Mimetic Inclinations - Rignano, Giulia Ulla (Critical horizons, 2023)
This article engages with Adriana Cavarero’s analysis of the Muse of Greek oral poetry to rethink the relationship between mimesis and narration, and the shaping power of the act of narration on the subject. I suggest that Cavarero’s reading of the Muse provides an understanding of mimesis that moves beyond representation to a form of contagion between embodied and temporal subjectivities. To clarify this, I show how Cavarero’s Muse anticipates her critique of rectitude in Inclinations and makes it clear that the inclined subject is not only the vulnerable and open subject as opposed to the vertical and autonomous one, but also the subject that has the power to incline the narratives that mimetically straighten it. The aim is to understand mimetic inclinations as destabilising voices of vertical narrations. As a concrete example of the troubling power of mimetic inclinations, I propose a rereading of Cavarero’s technique of theft presented in In Spite of Plato as a strategy of mimetic resistance.